Feno da folha de gliricídia na dieta de poedeiras semipesadas em restrição alimentar - Gurgel, Nathália Silva (2020)
This research aimed to evaluate the effects of the inclusion of gliricidia leaf-hay (GLH) in the diet of semi-heavy laying hens, in feed restriction, on performance, egg quality, quantity of phenolic compounds and yolk oxidation (TBARS) in fresh eggs. The experiment lasted for 6 periods of 21 days where bird performance evaluations and a metabolism test were made. For performance, 180 semi-heavy commercial hens (88 to 106 weeks old) were used in a completely randomized design, in a 2 x 2 + 1 factorial scheme. The treatments consisted on the interaction between two levels of feed restriction, 10 and 20%, and two ways to offer the FFG, ad libitum and mixed to the food in order to fulfill the restriction, and a control treatment, with 6 repetitions of 6 birds each. Significant differences were observed (P<0.05) in the performance variables, where food intake (FI) differed significantly from the control treatment, with the lowest intake observed when the GLH was offered mixed to the food with 20% of restriction, also resulting in the worst percentage results for laying, egg mass (EM) and feed conversion per egg mass (FC/EM) of this treatment, in addition to significant interactions (P <0.05) between the levels of restriction and the ways to offer the GLH under hay consumption, percentage of laying, EM and FC/EM. The restriction levels had no significant impact (P <0.05) on the voluntary intake of hay. A reduction in the coefficients of dry matter metabolization (DMMC), crude energy (CEC), ether extract (EEC), apparent metabolizable energy (AME) and apparent metabolizable energy corrected for nitrogen balance (AMEn) was observed in rations in treatments where the hay was mixed to the food in both restriction levels tested (10 and 20%). Significant interaction (P<0.05) between the restriction levels and the forms of offering the hay for the DMMC and CMEB was also observed. The treatments did not present significant differences (P <0.05) in the percentage of yolk and albumen, however, the restriction of 20% of the ration with mixed hay had a negative effect on the specific density (SD), % of shell and shell thickness (ST) and showed significant interaction (P <0.05) between restriction levels and forms of offering the hay in regard to SD. The yolk color increased significantly in the treatments in which the hay was included mixed to the food in both levels of restriction, with significant interaction (P <0.05) for the factors studied. The lipid oxidation of fresh egg yolks (TBARS) did not differ significantly (P <0.05) in any of the treatments. However, the amount of phenolic compounds showed a significant difference (P <0.05) for the treatment in which the birds ingested the highest proportion of hay in the diet (20% restriction and hay mixed to the food). The GLH can be used as a feed alternative in the diet of laying hens in feed restrictions of 10 and 20% for an ad libitum consumption, or it can be mixed with the feed when the concentrate reduction is of 10%